Legal Paradigm In The Standardization of Digital Payments: Between Technological Innovation and Monopoly Prevention In The Digital Era - Grace Yustisia Siahaan; Henny Yulienty (International Journal of Science and Environment (IJSE), 2026)
The rapid development of the digital economy has significantly transformed payment systems, marked by the increasing adoption of digital platforms and financial technologies. However, this transformation also raises concerns regarding market concentration, which may lead to monopolistic practices and the abuse of dominant positions, particularly due to network effects and closed ecosystem structures. This study aims to analyze the role of national digital payment system standardization as an instrument to prevent monopolistic practices from the perspective of competition law. The research employs a normative legal method, utilizing statutory and conceptual approaches, supported by comparative analysis of international practices. The findings indicate that standardization—especially when designed to be interoperable, open, and non-discriminatory—has significant potential to reduce barriers to entry, minimize consumer lock-in effects, and establish a level playing field among market participants. Nevertheless, its effectiveness largely depends on the regulatory design and implementation mechanisms. Poorly governed standardization may instead create new forms of market dominance, whether individually or collectively. Therefore, strong coordination between payment system authorities and competition law enforcement agencies is essential to ensure that standardization policies align with the principles of fair competition. This study concludes that national digital payment system standardization can function as a preventive instrument against monopolistic practices, provided that it is designed in an inclusive, adaptive, and competition-oriented manner, while still fostering innovation within the digital economic ecosystem.